2015
DOI: 10.1038/srep16958
|View full text |Cite
|
Sign up to set email alerts
|

Mimosoid legume plastome evolution: IR expansion, tandem repeat expansions and accelerated rate of evolution in clpP

Abstract: The Leguminosae has emerged as a model for studying angiosperm plastome evolution because of its striking diversity of structural rearrangements and sequence variation. However, most of what is known about legume plastomes comes from few genera representing a subset of lineages in subfamily Papilionoideae. We investigate plastome evolution in subfamily Mimosoideae based on two newly sequenced plastomes (Inga and Leucaena) and two recently published plastomes (Acacia and Prosopis), and discuss the results in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
135
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(150 citation statements)
references
References 67 publications
11
135
0
4
Order By: Relevance
“…In numerous angiosperm lineages, a subset of plastid genes, including clpP1 and accD, display accelerated evolutionary rates, but the causes of this recurring phenomenon have remained unclear (Jansen et al 2007;Erixon and Oxelman 2008;Greiner et al 2008b;Guisinger et al 2008Guisinger et al , 2010Guisinger et al , 2011Straub et al 2011;Sloan et al 2012aSloan et al , 2014aBarnard-Kubow et al 2014;Weng et al 2014;Dugas et al 2015;Williams et al 2015;Blazier et al 2016;Zhang et al 2016). We investigated the nuclear genes that contribute to the multisubunit complexes that include ClpP1 and AccD, and incorporated population genetic and structural data to distinguish between relaxed purifying selection and positive selection as drivers of elevated d N /d S values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In numerous angiosperm lineages, a subset of plastid genes, including clpP1 and accD, display accelerated evolutionary rates, but the causes of this recurring phenomenon have remained unclear (Jansen et al 2007;Erixon and Oxelman 2008;Greiner et al 2008b;Guisinger et al 2008Guisinger et al , 2010Guisinger et al , 2011Straub et al 2011;Sloan et al 2012aSloan et al , 2014aBarnard-Kubow et al 2014;Weng et al 2014;Dugas et al 2015;Williams et al 2015;Blazier et al 2016;Zhang et al 2016). We investigated the nuclear genes that contribute to the multisubunit complexes that include ClpP1 and AccD, and incorporated population genetic and structural data to distinguish between relaxed purifying selection and positive selection as drivers of elevated d N /d S values.…”
Section: Discussionmentioning
confidence: 99%
“…Within angiosperms, most plastid genomes are highly conserved in sequence and structure (Jansen et al 2007;Wicke et al 2011), but multiple independent lineages have experienced accelerated rates of aa substitution in similar subsets of nonphotosynthetic genes (Jansen et al 2007;Erixon and Oxelman 2008;Greiner et al 2008b;Guisinger et al 2008Guisinger et al , 2010Guisinger et al , 2011Straub et al 2011;Sloan et al 2012aSloan et al , 2014aBarnard-Kubow et al 2014;Weng et al 2014;Dugas et al 2015;Williams et al 2015;Zhang et al 2016). Several mechanisms have been hypothesized to explain these repeated accelerations including positive selection, reduced effective population size (N e ), altered DNA repair, changes in gene expression, and pseudogenization following gene transfer to the nucleus (see above citations).…”
mentioning
confidence: 99%
“…The boundary shifts in Eucommia ulmoides were hypothesized to be the result of genome rearrangement, whereas the shifts in the legumes were accompanied by the presence of an increased number of tandem repeats in the genome (Dugas et al. , Wang et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparative plastome studies in embryophyte families showed that boundaries between the IR and single copy regions are not static, but rather have been subjected to dynamic and random processes that allow the conservative expansion and contraction of IR regions. Movement of IR boundaries is likely to be unique for each species, and hypothesized to reflect relationship among embryophyte families (Zhu et al 2015, Wang et al 2016) and contribute to the expansion of the genome (Dugas et al 2015, Zhu et al 2016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation